2016
DOI: 10.1016/j.jtice.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of superhydrophobic sand: Potential advantages for practical application in oil–water separation

Abstract: Development of cost-effective and handy functional materials that can separate oil from water readily by a convenient method is highly desirable and still challenge. Herein, sand-based superhydrophobic surfaces were easily achieved by coating sand particles with silane, and the whole fabrication process was time-saving and facile to carry out. The superhydrophobic surfaces can be applied as an oil sorbent scaffold to absorb oil from water selectively because of their water-repelling and oil-attracting properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 34 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…Increasing the wetting characteristics of sand or PU sponge for organic phases is an active challenge in materials science and is a requirement for them to be applicable in the petroleum industry. It has been previously reported that superhydrophobic sand with different degrees of wettability can be used in the separation of emulsions or treatment of contaminated water [ 41 ]. The fabrication of superhydrophobic porous materials based on the PU sponge has great potential for oil absorption owing to their good stability, high absorption capacity, and recyclability [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the wetting characteristics of sand or PU sponge for organic phases is an active challenge in materials science and is a requirement for them to be applicable in the petroleum industry. It has been previously reported that superhydrophobic sand with different degrees of wettability can be used in the separation of emulsions or treatment of contaminated water [ 41 ]. The fabrication of superhydrophobic porous materials based on the PU sponge has great potential for oil absorption owing to their good stability, high absorption capacity, and recyclability [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, scientists also developed superhydrophobic sand for civil engineering and other applications. Men et al fabricated superhydrophobic sand by adding octadecyltrichlorosilane into the preparation solution [119]. These sands demonstrated a WCA of 154.8 ± 1 • and an SA of 4.5 ± 0.9 • , which can be used for oil/water separation.…”
Section: Stone and Sandmentioning
confidence: 99%
“…Men X.H. et al [ 11 ] used octadecyltrichlorosilane to hydrophobically modify sand. Due to the extremely fine particle size of the sand used, it exhibited superhydrophobic properties, but the scholars mainly applied it in the field of oil–water separation.…”
Section: Introductionmentioning
confidence: 99%